2013
DOI: 10.1007/s00442-013-2760-2
|View full text |Cite
|
Sign up to set email alerts
|

Predator facilitation or interference: a game of vipers and owls

Abstract: In predator-prey foraging games, the prey's reaction to one type of predator may either facilitate or hinder the success of another predator. We ask, do different predator species affect each other's patch selection? If the predators facilitate each other, they should prefer to hunt in the same patch; if they interfere, they should prefer to hunt alone. We performed an experiment in a large outdoor vivarium where we presented barn owls (Tyto alba) with a choice of hunting greater Egyptian gerbils (Gerbillus py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 27 publications
0
21
1
1
Order By: Relevance
“…Instead, the results likely reflect the behavioral plasticity of predators that enables them to capitalize on short-term changes in prey vulnerability. Our findings thus suggest that predator facilitation may prompt predators to increase their activity in their preferred habitat in the presence of other predators that hunt the same prey (Embar et al, 2014 , 2000). Thus, the roughly 50% increase in lynx deer kills we found during the hunting season implies that each lynx would kill five additional deer during the 10-week hunting period.…”
Section: Predictions 2 and 3: Increased Lynx Activity And Predationmentioning
confidence: 80%
See 1 more Smart Citation
“…Instead, the results likely reflect the behavioral plasticity of predators that enables them to capitalize on short-term changes in prey vulnerability. Our findings thus suggest that predator facilitation may prompt predators to increase their activity in their preferred habitat in the presence of other predators that hunt the same prey (Embar et al, 2014 , 2000). Thus, the roughly 50% increase in lynx deer kills we found during the hunting season implies that each lynx would kill five additional deer during the 10-week hunting period.…”
Section: Predictions 2 and 3: Increased Lynx Activity And Predationmentioning
confidence: 80%
“…The activity and hunting strategy of predators themselves may depend on whether other predators feeding on the same prey co‐occur or not (Matsuda, Abrams, & Hori, ). For example, Embar, Raveh, Hoffmann, and Kotler () showed experimentally that vipers ( Cerastes cerastes ) and owls ( Tyto alba ), both predators of gerbils ( Gerbillus pyramidum ), adjust their hunting activity depending on the presence of the other predator. By doing so, both predators may be able to improve their own hunting success.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, prolonged bouts of tail flagging may be costly because they could draw the attention of other predators (Broom and Ruxton 2012). Thus, rattlesnake-induced tail flagging may facilitate attacks from other predatory species (e.g., Kotler et al 1992;Embar et al 2014), which pups should avoid due to their high vulnerability. Associative learning facilitated by conspecifics is likely the main process by which pups develop adult-like snake responses.…”
Section: Snake-interaction Behaviorsmentioning
confidence: 99%
“…Our results show that both predator facilitation and antipredatory behaviours are involved in interactions between weasels and avian predators. Such behavioural responses to the presence of intraguild predators can further cause risk enhancement or reduction in shared prey (Charnov et al ., ; Kotler et al ., ; Korpimäki et al ., ; Embar et al ., ). In an earlier study, we observed risk reduction in shared prey between owls and weasels (Hoset et al ., ), suggesting that hunting simultaneously did not improve the hunting efficiency of the predators.…”
Section: Discussionmentioning
confidence: 98%
“…Bischof et al ., ), whereas interactions between predators with different hunting strategies often show positive effects (e.g. Korpimäki et al ., ; Embar et al ., , this study). We recommend that studies on multi‐predator effects need to assess the dominance of predator hunting modes and relationships between small and large predator species to obtain a full perspective of these effects.…”
Section: Discussionmentioning
confidence: 99%